Rancang Bangun Rombong Listrik Dengan Menggunakan Pembangkit Listrik Tenaga Surya (PLTS) Kapasitas 200 Watt - Dewananta, Alvin Rivada; Rahmadhani, Rian Agung; Fantoja, Dimas Maulana; Muharom, Muharom; Setyono, Gatot (Journal of System Engineering and Technological Innovation, 2022)
The solar energy that reaches the earth in one hour is sufficient to meet the energy needs of all humans on the earth's surface in one year, reason enough to spur the maximization of solar energy like renewable energy, especially by converting it into electricity by cell devices/solar panels. To get the maximum output of solar cell panel energy by optimizing the direction of the solar cell panels to the sun. The solution is to design a tracking system that adjusts the position of the solar cell panels automatically following the sun based on Arduino Uno R3. The method used is to compare the two solar cell panels using the Arduino Uno R3. tracking system and solar cell panels without a tracking system. From the two measurement results in the morning to afternoon, it was found that the panel using the tracking system had a total power output of 104.3364 Watt and the panel without a tracking system had a total power output of 43.05094 Watt, so from the results of the most optimal measurement, the panel using the tracking system. It can be seen in measurements from 09.30 WIB to 16.30 WIB solar cell panels using a tracking system produce greater energy output than solar cell panels without a tracking system, an increase in the power output compared to panels.